2011
DOI: 10.1038/cddis.2011.18
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in ApoE-deficient mice progresses independently of the NLRP3 inflammasome

Abstract: The interleukin-1 (IL-1) family of cytokines has been implicated in the pathogenesis of atherosclerosis in previous studies. The NLRP3 inflammasome has recently emerged as a pivotal regulator of IL-1β maturation and secretion by macrophages. Little is currently known about a possible role for the NLRP3 inflammasome in atherosclerosis progression in vivo. We generated ApoE−/− Nlrp3−/−, ApoE−/− Asc−/− and ApoE−/− caspase-1−/− double-deficient mice, fed them a high-fat diet for 11 weeks and subsequently assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
167
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(171 citation statements)
references
References 23 publications
(22 reference statements)
2
167
1
1
Order By: Relevance
“…It has been reported that dyslipidemia attenuates EC proliferation in vitro and angiogenesis in vivo (14 -16). Although the role of caspase-1 in the dyslipidemic environment and atherogenesis remains controversial (31), the dominant concept supported by our own report (9) is that caspase-1 plays a proatherogenic role, which is supported by results collected from apoE Ϫ/Ϫ /caspase-1 Ϫ/Ϫ mice (9,32,33) (33) studied the role of caspase-1 deficiency in full-blown atherosclerosis in apoE Ϫ/Ϫ mice after high fat feeding for 8 weeks (32) and 12 weeks (33). The differences of endothelial cell sizes were observed previously (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dyslipidemia attenuates EC proliferation in vitro and angiogenesis in vivo (14 -16). Although the role of caspase-1 in the dyslipidemic environment and atherogenesis remains controversial (31), the dominant concept supported by our own report (9) is that caspase-1 plays a proatherogenic role, which is supported by results collected from apoE Ϫ/Ϫ /caspase-1 Ϫ/Ϫ mice (9,32,33) (33) studied the role of caspase-1 deficiency in full-blown atherosclerosis in apoE Ϫ/Ϫ mice after high fat feeding for 8 weeks (32) and 12 weeks (33). The differences of endothelial cell sizes were observed previously (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…21 However, another study found that although cholesterol crystals induced IL-1␤ release, no difference in atherosclerosis occurred when mice without inflammasome components were crossed onto ApoE Ϫ/Ϫ . 35 Lastly, recent work has demonstrated that basic calcium phosphate crystals also activate NLRP3 inflammasomes, suggesting that calcification may also serve as an important DAMP in vascular disease. 36 Revascularization after myocardial infarction triggers a massive inflammation that contributes up to 50% of the infarct area.…”
mentioning
confidence: 99%
“…Because in this model a more severe cholesterol-rich diet was used, it is possible that other redundant mechanisms that contribute to atherosclerosis development obscured the NLRP3 phenotype. 211 Notably, the danger signals that activate the inflammasome to elicit IL-1β release can also induce IL-1α secretion. Depending on the type of inflammasome activator, release of IL-1α was inflammasome-dependent or inflammasomeindependent.…”
Section: Nlrs and Inflammasomesmentioning
confidence: 99%